The Influence of Teacher Performance on Student Interest in Class XI Labor Vocational Schools Assisted by FKIP UNRI - Siagian, Shehana; Hambali, Hambali; Arianto, Jumili (Journal of Education Technology Information Social Sciences and Health, 2024)
This research is motivated by the low quality of teacher performance, apart from that theoretically students' interest in learning is also influenced by teacher performance. Interest in learning is a person's pleasure, passion and interest in carrying out learning activities. In order for teaching activities to be accepted by students, teachers need to try to arouse students' interest in learning. In the process of increasing interest in learning, it is not easy because each student has a different character. Good teacher competence is needed so that teachers are more creative in finding teaching methods to increase students' interest in learning. The aim of the research is to find out whether there is an influence of teacher performance on the learning interest of class XI students at the Labor Vocational School under the guidance of FKIP UNRI. This type of research uses an associative quantitative approach, with data collection techniques using questionnaires, documentation, interviews and literature studies. Based on analysis of research data, it was found that the F test produced ???????????????? = 4.10 and ????ℎ???????? = 7.13. Because ????ℎ???????? is greater than ????????????????, it can be concluded that Ho is rejected and Ha is accepted. Based on this statement, the research hypothesis is accepted, namely that teacher performance (variable X) has a positive influence on student interest in learning (variable Y). Apart from that, the influence of teacher performance on students' interest in learning is at a moderate level. Based on the calculation results above, it is clear that the relationship value (R) is 0.39. Thus, a coefficient of determination (R Square) of 0.15 is obtained, which means that the independent variable (Teacher Performance) to the dependent variable (Students' Learning Interest) is 15.80%. Based on the results and discussion in this research, it can be concluded that teacher performance has a positive influence on the learning interest of class